Characterization of signs and symptoms of childhood cancer: The perception of the parents of affected children (Research, Society and Development, 2021)
Objective: To know the signs and symptoms of childhood and adolescent cancer perceived by the parents of those affected and the time between seeking a health service and the diagnosis of the disease. Methodology: Cross-sectional study, of exploratory nature and quantitative approach, through registration database, standardized by AVOSOS, carried out in the period of December 2019, which includes the parents of children and adolescents, between 0 and 19 years old, in treatment for malignant neoplasms, assisted by the institution, at the time of admission. Results: 719 children and adolescents participated in the study. Fever (40%) and pain (38.1%) were the signs and symptoms most reported by parents, followed by headache, vomiting, asthenia and tumors. Seeking medical care occurred within one month in 79.6% and cancer diagnosis occurred within 1 to 3 months of symptom onset in 39.9%. Leukemia and lymphoma were the most frequent neoplasms. Neuroblastoma, bone tumors, CNS tumors, soft tissue tumors, and other sarcomas were most responsible for deaths. The most common treatments performed for CIJ patients were chemotherapy and surgical procedures, respectively. Conclusion: Fever, one of the initial manifestations of leukemia, the most common neoplasm, is the main symptom leading to medical attention. Seeking medical service occurred within one month of symptom occurrence and diagnosis between one and three months after symptom onset, however, seeking after one month of first symptom in a significant portion of the population merits concern.